IMPORTANCE OF EFFICIENT OPERATION NOTE WRITING: REVIEW OF GUIDANCE - Younis, Muhammad Umar (Journal of Ayub Medical College Abbottabad, 2021)
Background: Operative notes are the most important account of a surgical procedure containing all details that may have been encountered during the surgery. Summary: Below par quality of these notes remains a challenge for the healthcare system and guidelines from the Royal College of Surgeons should be made use of to ensure efficient recording. Operative notes need to be legible with clear and concise instructions for the nursing staff for postoperative care. Key messages: Relevant details of surgery, additional procedures and complications should be thoroughly documented as well to avoid losses in terms of financial remuneration and for medicolegal purposes. Residents in training should be taught about their importance and inclusion in surgical curriculum should be sought. Keywords: Documentation; Guidance; Note writing; Operation note; Surgery